Analisis Perbandingan Antara Metode FCFS, SPT Dan EDD Pada Pengolahan Biji Kopi Kering - Healthy Aldriany Prasetyo; Rafael Remit Winardi (BEST Journal (Biology Education, Sains and Technology), 2023)
The aim of this study was to determine the best method for using huller coffee bean processing machines at PT. XYZ. Huller is a tool used to peel dry coffee bean skin. The methods used are FCFS, SPT and EDD. The First Come First Served (FCFS) method is where work is processed based on the arrival of the material to be processed. The Shortest Processing Time (SPT) method starts with recording customer orders based on the shortest processing time. The Earlier Due Date (EDD) method starts with recording customer orders based on the due date. Selection and determination of the method used for huller operations based on the arrival of raw materials, processing time and maturity time of customer orders. The data collected consists of the number and capacity of the hullers owned, the volume of raw materials, available working hours and processing time. Processing effectiveness is measured based on: average completion time, average number of jobs, product processing time, average delay and utility. The results showed that the FCFS method was the best method compared to the SPT and EDD methods in the process of stripping the dry seed coat by 5 (five) huller units.